Parotid abscess secondary to brucellosis in a patient with primary Sjogren's syndrome - Yolbas, Servet; Bozgeyik, Zulkif; Artas, Gokhan; Koca, Suleyman Serdar (Aves, 2018)
Swelling in the salivary glands, particularly parotid glands, is observed in approximately one third of Sjogren's syndrome patients. However, such patients should be assessed in terms of causes such as malignancies, infections, amyloidosis, sarcoidosis, and other autoimmune diseases when parotid gland swelling is noted. It should be considered that the incidence of lymphoma increases in Sjogren's syndrome. Unilateral parotid swelling, especially if accompanied by severe pain and redness, should be monitored for suppurative bacterial infections. Brucellosis is a systemic disease that may involve one or multiple organs. It can appear with different clinical manifestations and nonspecific symptoms. Although local abscess formations secondary to brucellosis in different organs have been reported, no evidence for parotid involvement has yet been reported. In this study, a case with primary Sjogren's syndrome and parotid abscess secondary to brucellosis is presented.
Keywords: Sjogren's syndrome; parotid; brucellosis